Conjugation of Short-Chain Fatty Acids to Bicyclic-Amines for Analysis by Liquid Chromatography Tandem Mass Spectroscopy - Daniel N. Darlington (Molecules)
Conjugation of short-chain fatty acids (SDFAs) to amines containing ring structures allows for better measurement by liquid chromatography tandem mass spectroscopy (LC-MS/MS). However, collision-induced dissociation (CID) results in breaking the conjugate back to the original SCFA and amine. We therefore set out to find an amine that would remain on the SCFA after CID and create a unique daughter for selectivity of measurement. Of twenty-seven amines with ring structures, we found four that contain bicycle-type structures (two rings connected by a carbon) with nitrogen in the second ring. CID removes the second ring at the nitrogen, leaving the first ring on the daughter. Of the four amines, 4-(pyrrolidine-1-ylmethyl) benzylamine (4PyBA) showed the strongest conjugation. Conjugation of 4PyBA to SCFA (C3–C6), their isomers and their phenylated versions (and isomers) resulted in good chromatographic peaks and separation. CID resulted in unique daughters that allowed for selectivity of measurement. Using this method, standard curves were generated that show good linearity (r2 > 0.99) in the nM and μM range with lower limits of detection between 40 and 229 nM for a 10 μL sample. Finally, we used this method to measure SCFA in plasma, liver, platelets, and red blood cells, demonstrating its use in biological systems. Because SCFAs are an index of microbiome diversity in the gastrointestinal track, this method will allow us to study changes in SCFAs and the microbiome in pathologic conditions including trauma, hemorrhage, and sepsis.